The Analysis of Total Leucocyte, C-Reactive Protein and Fibrinogen Concentrations to Evaluate The Leakage of Enterectomy Result - Dhirgo Adji (Jurnal Sain Veteriner, 2012)
Enterectomy is an operative method that has very dangerous risk. The purpose of this research was done to see the physiological view after surgery, especially in the total leucocyte, C-reactive protein (CRP) andfibrinogen concentrations. Nine female, healthy local dogs, 10 kgs of body weight were used as experimental study. The dogs were adapted for a week into individual cages and fed commercial dog-food and water adlibitum. In the day of 7, all dogs were fasted 12 hours for anaesthesia preparation. The dogs were then divided into 3 Groups of 3 each. Group I was used as control, it had normal enterectomy surgery. Group II was animals that had enterectomy surgery with one hole leakage. Group III was animals that had enterectomy surgery with two special hole leakages. Enterectomy itself was done on to jejunum with 5 cm of gut should be cut away. Anastomosis method was done using end to end method and interrupted suturing method with chromic cat gut 0/3. The result of the research showed that there is similarly increasing level of leucocyte and CRP in the second day after surgery and decreased gradually until the sixth day, but different type of changes in fibrinogen level. The increasing level of CRP has advantages, such as it can be used as eidker marker of inflammation or infection, or worse condition after enterectomy.Keywords : enterectomy, leucocyte, C-reactive protein, fibrinogen, inflammation